Teach Yourself Jung : The Key Ideas - Ruth Snowden (Teach yourself books (Lincolnwood, Ill.), 2010)
Jung - the Key Ideas will quickly familiarize you with the revolutionary thinking of this great man. It will teach you all the essential concepts, from the collective unconscious to archetypes in dreams. Expressing Jung\'s sometimes complex ideas in simple terms, and backed up with references to his own texts, this book gives you everything you need to know. NOT GOT MUCH TIME? One, five and ten-minute introductions to key principles to get you started. AUTHOR INSIGHTS Lots of instant help with common problems and quick tips for success, based on the author\'s many years of experience. FIVE THINGS TO REMEMBER Quick refreshers to help you remember the key facts. TRY THIS Innovative exercises illustrate what you\'ve learnt and how to use it.